2015
DOI: 10.3329/dujbs.v24i2.46323
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic potential of rhizosphere mycoflora against Fusarial wilt of brinjal

Abstract: Antagonistic potentials of seven rhizoshere soil fungi viz., Aspergillus flavus Link., A. fumigatus Fresen., A. niger Tiegh., A. terreus Thom., Penicillium sp., Trichoderma harzianum Refat. and T. viride Pers. were tested against the Fusarium oxysporum Schlecht. and F. solani (Mart.) Sacc. – the two pathogens, isolated from wilted roots of brinjal plants. Out of seven soil fungi Trichoderma harzianum was found most effective to control the growth of both the test pathogens. More than 50% inhibition of the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…The highest inhibition (57.36%) was recorded owing to T. harzianum against P. guepinii followed by F. moniliforme (46.80%), A. alternata (46%) owing to T. viride. The per cent inhibition owing to volatile metabolites of Trichoderma harzianum against the mycelial growth of C. lunata, D. oryzae, F. moniliformae, F. solani, M. oryzae, P. guepinii and S. oryzae were 46, 38.85, 37.14, 25, 36.25, 57.36 and 30.33 %, respectively.These results are in agreement with the findings Romana et al (2015) and Barakat et al (2013). Romana et al (2015) reported that highest inhibition of radial growth of F. solani and F. oxysporum was found due to T. harzianum followed by T. viride and A. niger, respectively.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The highest inhibition (57.36%) was recorded owing to T. harzianum against P. guepinii followed by F. moniliforme (46.80%), A. alternata (46%) owing to T. viride. The per cent inhibition owing to volatile metabolites of Trichoderma harzianum against the mycelial growth of C. lunata, D. oryzae, F. moniliformae, F. solani, M. oryzae, P. guepinii and S. oryzae were 46, 38.85, 37.14, 25, 36.25, 57.36 and 30.33 %, respectively.These results are in agreement with the findings Romana et al (2015) and Barakat et al (2013). Romana et al (2015) reported that highest inhibition of radial growth of F. solani and F. oxysporum was found due to T. harzianum followed by T. viride and A. niger, respectively.…”
Section: Resultssupporting
confidence: 94%
“…It is known to be capable of producing antibiotics which might have suppressed the growth of the test pathogens. These findings are in consistent with the findings of Skidmore andDickinson (1976), Adriana andSergio (2001), Kexiang et al (2002), Krupke et al (2003), Shafiquzzaman et al (2009), Akter et al(2014, Bashar and Chakma (2014) and Romana et al (2015). Considering the findings of the present experiment, Trichoderma harzianum could be used as a commercial bio control agent against rice pathogens.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation